2001
DOI: 10.1080/00305364.2001.11745251
|View full text |Cite
|
Sign up to set email alerts
|

Assessing service quality in paediatric audiology and early deaf education

Abstract: Quality monitoring and assurance is a key aspect of evidence-based service provision in health and education. Part I of the present paper summarizes the results from a survey in which performance of health-based paediatric audiology services in the UK was assessed against existing good practice guidelines (NDCS, 1994, 1996). The results of the survey indicated varied levels of provision, with guidelines commonly not followed. Part II of the paper reports the detailed development of two short questionnaires des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…This indicates lack in target ages for diagnosis and intervention. Similar finding was also reported in a survey assessing readiness for universal neonatal screening in the United Kingdom whereby 50% of the respondents did not have target age of intervention [17]. Determining true hearing level and making a decision on fitting hearing aids in babies with milder degree of hearing loss can be a challenge especially for audiologists who are new in the field of pediatric audiology.…”
Section: Ages Of Diagnosis and Interventionsupporting
confidence: 81%
See 1 more Smart Citation
“…This indicates lack in target ages for diagnosis and intervention. Similar finding was also reported in a survey assessing readiness for universal neonatal screening in the United Kingdom whereby 50% of the respondents did not have target age of intervention [17]. Determining true hearing level and making a decision on fitting hearing aids in babies with milder degree of hearing loss can be a challenge especially for audiologists who are new in the field of pediatric audiology.…”
Section: Ages Of Diagnosis and Interventionsupporting
confidence: 81%
“…Implementing a universal hearing programme may look easy on the outset and this has produced a strong movement to develop hearing screening programme even in hospitals where follow-up services are questionable. A survey in the United Kingdom revealed that 9 of the 14 sites who claimed they were ready to participate in UNHS were among the poorest service providers in the study [17]. It must be stressed that screening is only the first step to rehabilitation.…”
Section: Ages Of Diagnosis and Interventionmentioning
confidence: 98%
“…Many existing treatment or intervention services evolved prior to the current focus on UNHS, the availability of current hearing technology, and the emphasis on evidence-based practice. Research undertaken in the United Kingdom in preparation for a new UNHS program revealed several barriers to the implementation of UNHS both from professionals' and parents' perspectives (Bamford et al, 2001;Robinshaw & Evans, 2003). In the United States, the referral of families for early intervention has been described as the weakest link in the EHDI system (Sass-Lehrer, 2004).…”
mentioning
confidence: 99%
“…Pesquisadores (24) apresentaram uma proposta de avaliação da qualidade de centros de saúde auditiva infantil na Inglaterra, por meio de questionário aplicado nos serviços do país. Embora algumas instituições estivessem atuando em consonância com a Política de Atenção à Saúde preconizada no país, os resultados obtidos revelaram grande variabilidade na qualidade dos serviços e, conseqüentemente, na intervenção audiológica concedida às crianças deficientes auditivas e suas famílias.…”
Section: Perspectivas Na Avaliação Dos Serviços De Saúde Auditivaunclassified